Discrete Emotions and Persuasion: The Role of Emotion-Induced Expectancies. - DeSteno, David; Wegener, Duane T.; Petty, Richard E. (Journal of Personality & Social Psychology, 2004)
The authors argue that specific emotions can alter the persuasive impact of messages as a function of the emotional framing of persuasive appeals. Because specific emotions inflate expectancies for events possessing matching emotional overtones (D. DeSteno, R. E. Petty, D. T. Wegener, & D. D. Rucker, 2000), the authors predicted that attempts at persuasion would be more successful when messages were framed with emotional overtones matching the emotional state of the receiver and that these changes would be mediated by emotion-induced biases involving expectancies attached to arguments contained in the messages. Two studies manipulating discrete negative emotional states and message frames (i.e., sadness and anger) confirmed these predictions. The functioning of this emotion-matching bias in parallel with emotion-induced processing differences and the limitations of a valence-based approach to the study of attitude change are also considered. Reprinted by permission of the publisher.